Immigrant-Conscious Congregations: Race, Ethnicity, and the Rejection of Anti-Immigrant Frames - Brown, R. Khari (Politics and religion, 2017)
Using data collected between 2004 and 2008 from the National Politics Studies, this study explores the impact of race on the likelihood of attending worship settings that provide supportive services for and preach sermons about immigrants. It also considers the degree to which attending such worship settings associate with the perceptions that Whites, Blacks, and Hispanics hold of immigrants. We find that while Hispanics are more likely than Whites and Blacks to attend such immigrant-conscious congregations, attending such congregations more strongly correlates with Whites rejecting anti-immigrant frames and accepting positive frames than is the case for Blacks and Hispanics.